Discrete fracture analysis using locally refined T‐splines. (2nd August 2018) - Chen, L.; Verhoosel, C. V.; de Borst, R.
Summary: Locally refined T‐splines are used to model discrete crack propagation without a predefined interface. The crack is introduced by meshline insertions in the locally refined T‐mesh, which yields discontinuous basis functions. To implement the method in existing finite element programs, Bézier extraction is used. A detailed description is given as to how the crack path is inserted and how the domain is reparameterized after insertion. The versatility and accuracy of the approach to model discrete crack propagation without the crack path being predefined is demonstrated by two examples, namely, an L‐shaped beam and a single‐edge notched beam. When the crack approaches the physical boundaries, limitations to reparameterization arise, as will be discussed at the hand of a double‐edge notched specimen.